LEVI's Factory Outlet Phenomenon in Indonesia - Hanif, Hanif; Hudrasyah, Herry (Journal of Business and Management, 2013)
This Final project (Research) is about Leviâ€™s factory outlet in Indonesia which further abbreviated as LOS (Levi's Outlet Store). Factory outlet is a retail store in which manufacturers sell their products directly to the public as consumers. Factory outlets function is to increase sales and reduce inventory piling up in warehouses. The purpose of this study is to determine how much influence the Levi's outlet store on the phenomenon of factory outlets in Indonesia and to determine how much 7PS influence sale at Levi's outlet store. The research was conducted in LOS Bekasi (Bekasi Square), LOS Pejaten Village, LOS Plaza Cibubur and LOS Bogor using purposive sampling method. Purposive sampling is the selection of the sample is based on certain characteristics that are considered nothing to do with the characteristics of the population. Based on data collected from 400 respondents Levi's outlet store that has been deployed in LOS Bekasi (Jakarta Square), LOS Housing Village, LOS Plaza Cibubur and LOS Bogor then can be drawn some conclusions, that is the existence of Levi's outlet store in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) is one of the many FO growing in Indonesia and has a very large market opportunity. Now, Levi's products are become a lifestyle (trend) in the most of the Indonesian people and the existence of LOS provide convenience to customers to find the product Levi's product they likeÂ Keywords: Levi's Outlet Store,7PS, Factory Outlets, Indonesia customers